ANALISIS MODEL PENERIMAAN TEKNOLOGI DALAM PENGGUNAAN ONLINE MARKETSPACE SEBAGAI MEDIA PEMASARAN - Arif Sugiono; Prasetya Nugeraha; Jimly Majidi Asaif (Metakom, 2022)
The purpose of this study is to find out how technology acceptance is based on Perceived Ease Of Use and Perceived Usefulness of online marketspace (SHOPEE) as a marketing medium so that later it can be seen the Attitude Toward Using, Behavioral Intention To Use, as well as Actual System Usage in clothing boutiques in Bandar Lampung. The informants in this study are the management and employees of Lady Fame and Candy Lady Boutique Stores, as well as parties outside of two boutiques who are also active users of online market space (SHOPEE). The method in this study uses a qualitative approach to the type of descriptive research. Data obtained by interview, literature study and observation. With data analysis techniques using an interactive model. The data validity checking technique used is the type of source triangulation. The results of this study indicate that online market space technology (SHOPEE) has led to the Perceived Ease Of Use and Perceived Usefulness, while the Attitude Toward Using is considered good and leads to Behavioral Intention To Use. So that the real condition of the Actual System Usage raises a fairly high intensity in its use as a marketing medium.